2020
DOI: 10.1055/s-0039-3402761
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism and the Risk of Venous Thromboembolism: A Nationwide Cohort Study

Abstract: Background Previous studies have shown that hypothyroidism may have an impact on blood coagulation. However, how hypothyroidism and thyroxine replacement therapy (TRT) affect the risk of venous thromboembolism (VTE) remains controversial. This study aimed to examine the associations of hypothyroidism and TRT with VTE risks. Materials and Methods This nationwide population-based cohort study was conducted using Taiwan's National Health Insurance Research Database. We enrolled 10,818 hypothyroid patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…24 Importantly, this study found that this increased risk was negated with use of thyroid replacement therapy (aHR 0.34 [95% CI 0.13-0.88]). 24 In the perioperative context, correction of existing endocrinopathies, when possible, may represent an actionable strategy to mitigate risk of VTE, particularly if chemoprophylaxis is not a desirable option.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…24 Importantly, this study found that this increased risk was negated with use of thyroid replacement therapy (aHR 0.34 [95% CI 0.13-0.88]). 24 In the perioperative context, correction of existing endocrinopathies, when possible, may represent an actionable strategy to mitigate risk of VTE, particularly if chemoprophylaxis is not a desirable option.…”
Section: Discussionmentioning
confidence: 73%
“…A recent study of 10,818 patients found a significantly higher association between hypothyroidism and VTE, with an adjusted hazard ratio (aHR) of 1.83 (95% CI 1.44–2.33) 24 . Importantly, this study found that this increased risk was negated with use of thyroid replacement therapy (aHR 0.34 [95% CI 0.13–0.88]) 24 . In the perioperative context, correction of existing endocrinopathies, when possible, may represent an actionable strategy to mitigate risk of VTE, particularly if chemoprophylaxis is not a desirable option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 50% of VTEs are provoked by immobilization, trauma, surgery, or hospitalization in previous 3 months [12][13][14][15], and 20% associated with cancer while 30% unprovoked [16][17][18]. VTE has many risk factors which are constantly multiplied [19][20][21][22][23][24][25]. Currently, Caprini Risk Assessment Scale is widely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…And 20% are associated with cancer while 30% are unprovoked [16][17][18]. VTE has many risk factors which are constantly being updated [19][20][21][22][23][24][25]. Currently, Caprini Risk Assessment Scale is widely used in clinical practice.…”
mentioning
confidence: 99%